Size effects in the CO sensing properties of nanostructured TiO2 thin films fabricated by colloidal templating - Moon, Hi Gyu; Jang, Ho Won; Kim, Jin-Sang; Park, Hyung-Ho; Yoon, Seok-Jin (Electronic materials letters, 2010)
This study investigates the CO sensing properties of nanostructured TiO 2 thin film gas sensors fabricated with colloidal templates using different sizes of polymer spheres. Compared to plain films, the nanostructured films show enhanced gas sensing in the form of greater sensitivity and a faster response. More interestingly, the use of colloidal templates with smaller spheres (300 nm in diameter) leads to close-packed nanostructured TiO 2 thin films with very large-scale uniformity and a more pronounced improvement in CO sensing compared to the use of larger spheres (1 μm in diameter). This result suggests that an understanding of the sphere size effects on the gas sensing properties of nanostructured TiO 2 thin films created by colloidal templating is important in the development of these films for actual applications.